Microstructural Alterations In The Lymphoid Organs Of The Periadolescent Rats After Experimental Exposure To The Repeated And Variable Stressors - Kapitonova, Marina; Nor-Ashikin, M. N. K.; Fuad, S.B; Kuznetsov, S.L; Dydykin, S.S. (Indo American Journal of Pharmaceutical Sciences(IAJPS), 2019)
Recent investigations demonstrated that chronic variable stressors exhibit more severe effect on the endocrine and immune systems of the body compared the repeating stressors. During adolescent period of life lymphoid organs undergo fast developmental changes which may overlap with stress-induced immunomodulation. The influence of different chronically applied stressors on the lymphoid organs during various phases of periadolescence requires further investigation. The objective of this research is to evaluate immunomodulatory effect of variable vs. repeating stressors on the morphology of the lymphoid organs in periadolescent experimental animals of different age. Repeating or variable stressors were applied for 9 days continuously to the infant and early pubertal rats. Central (thymus) and peripheral (spleen) lymphoid organs were sampled and evaluated using morphometry of the immunologically stained histological sections. Chronic variable stressors exposure showed more significant immunosuppressive effect in the thymus and spleen of the infant rats compared to the early pubertal ones, as demonstrated by more significant decrease of the volume density of different populations of immunocytes in the thymus and the spleen, and an increase of the density of caspase-3-positive cells in the spleen. Comparative evaluation of the repeating stressor exposure revealed significant reduction of the volume density of the CD20+ lymphocytes and increased apoptotic rate in the spleen of both age groups; CD45RC+ lymphocytes in the thymus and CD4+, CD8+ and CD90+cells in the spleen were reduced in the infant rats only, while in early pubertal rats reduction was not significant compared to the control animals. This microscopic study shows that different neuroendocrine consequences of chronically applied variable vs. repeating stressors during various periods of early age induce complex age-dependent immunomodulation due to the overlapping of the developmental changes and post-stress alterations in the central and peripheral lymphoid organs in the immature body of the experimental animals.